The Late Middle and Early Upper Palaeolithic in Crimea (Ukraine) – A Review of the Neanderthal Refugium Hypothesis - Pigott, Emily M.; Uthmeier, Thorsten; Chabai, Victor P.; Higham, Thomas (Journal of Paleolithic Archaeology, 2024)
The Crimean Peninsula contains numerous important Palaeolithic sites. It has been considered a potential Neanderthal refugium in Eurasia prior to their disappearance or assimilation, and subsequent replacement by Homo sapiens. This understanding is primarily drawn from lithic technological analysis and radiocarbon dating. However, recent developments in the latter suggest that many of the previously obtained radiocarbon dates from Crimean sites may be too young. The chronological sequence from the site of Kabazi II is a case in point, where differences between dates of bulk collagen and those of single amino acids range up to 10,000 radiocarbon years. These discrepancies are argued to arise from sample contamination and its lack of removal in bulk collagen dating. In this paper, we undertake a critical re-evaluation of results from seven Palaeolithic archaeological sites in the Crimean Peninsula: Kabazi II, Siuren I, Buran-Kaya III, Zaskalnaya V and Zaskalnaya VI, Kabazi V and Starosel’e. Our analysis of radiocarbon results from various sites supports the view that radiocarbon dates obtained so far tend to be too young, which has been indicated in the stratigraphy and lithic assemblages. By harnessing robust radiocarbon protocols in future chronometric work, such as the extraction of hydroxyproline, ninhydrin derivatisation or the purification of amino acids using XAD-2 resin, there is potential for constructing accurate chronologies. Furthermore, improved dating accuracy holds the promise of significant additional insights into the prehistoric sequence of the Crimean Peninsula and its potential role as a refugium for Neanderthals prior to their disappearanc